2000
DOI: 10.1007/s002960000059
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac involvement in patients with Wegener's granulomatosis

Abstract: Wegener's granulomatosis (WG) is a systemic necrotizing vasculitis, which could potentially affect any organ system. However, there have only been a few reports on cardiac involvement. We described the echocardiographic findings in nine patients affected by WG. A complete M-mode, two-dimensional, Doppler and color-Doppler transthoracic echocardiogram was performed in nine patients (seven females and two males) affected by WG. In each patient, cardiac abnormality, for example, valvular damage, left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 11 publications
3
52
0
Order By: Relevance
“…Other findings included valvulitis, left ventricular aneurysm and a large intracardiac mass (34,35). In another study conducted by Morelli et al, of nine GPA patients with echocardiography, aortic valve thickening in eight patients was detected (14). Likewise, Kosovsky et al, reported a 16-year-old boy who was diagnosed as GPA after a cardiac mass had been detected and the pathological examination had revealed granulomatous vasculitis (13).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other findings included valvulitis, left ventricular aneurysm and a large intracardiac mass (34,35). In another study conducted by Morelli et al, of nine GPA patients with echocardiography, aortic valve thickening in eight patients was detected (14). Likewise, Kosovsky et al, reported a 16-year-old boy who was diagnosed as GPA after a cardiac mass had been detected and the pathological examination had revealed granulomatous vasculitis (13).…”
Section: Discussionmentioning
confidence: 98%
“…Lungs in 72%, kidneys in 36% and eyes in 24%, while heart involvement was found in only 8% of cases (13). Cardiac involvement may be subclinical or the principal source of symptoms (14,15). It usually occurs late in the course of the disease but it may also be the first manifestation (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The few case reports and general reviews show that the two most common cardiac manifestations are pericarditis and coronary arteritis (50% of cases), but myocarditis, endocarditis, and conduction system disturbances are also described [10][11][12][13].…”
Section: Cardiac Manifestation In Granulomatosis With Polyangiitismentioning
confidence: 99%
“…1 According to different studies, echocardiographic abnormalities due to cardiac involvement in GPA is relatively common, including systolic dysfunction, pericardial effusion, valvular involvement and so far. 7,8 Nonbacterial thrombotic endocarditis (NBTE) is a rare manifestation of GPA and to our knowledge its concomitant presentation with myocarditis is not reported to date. Herein, we report a case of GPA, who diagnosed with both myocarditis and NBTE.…”
Section: Introductionmentioning
confidence: 99%